Oprema mestnih javnih prostorov na Poljskem - Banach-Ziaja, Marzena (Urbani izziv, 2008)
This article's focus on aesthetic side of public space includes the smallest elements of its equipment. It is furnishings that have significant influence on the final shaping. A tiny change sometimes provides complete makeover of an everyday space's image. Unfortunately, there are a lot of local services and authorities, which are responsible for its creation. Perhaps, their quantity is the cause of a visible lack of coordination of acts and initiatives, undertaken in some cities in Poland. That is why, a proper designing and selecting of details, ought to be seen as a solution of many problems concerning maintenance and usage of public spaces, not only in Polishcities.
Keywords: arhitekturni detajli; javni prostor; mesta; Poland; Poljska; prostorski razvoj; prostorsko urejanje; spremembe; urbani prostor